Effect of precursor solution on the formation of perovskite phase of Pb(Mg-1/Nb-3(2/3))O-3 thin films - Spagnol, P. D.; Varela, José Arana [UNESP]; Bertochi, MAZ; Stojanovic, B. D.; Tebcherani, S. M. (Elsevier B.V., 2002)
Precursor solutions for Pb(Mg1/3Nb2/3)O-3 (PMN) synthesis were obtained by Pechini's method. The influence of the concentration of organic materials on the phase formation has been studied. For this purpose, PMN solutions were prepared with different precursors and were characterized by thermogravimetric and differential thermal analysis. The obtained solutions were deposited onto a Si (100) substrate by dip coating and pre-treated in a hot plate at 300 degreesC for 1 h. The films were annealed at 600, 700, 800 and 900 degreesC for 1 h and characterized by X-ray diffraction. The perovskite phase was formed after annealing at 600 and 700 degreesC when the solution of PMN was prepared with a lower amount of organic material and starting with mobium oxide. By increasing the temperature to 800 or 900 degreesC, only the formation of pyrochlore phase was observed. With the solution prepared from mobium ethoxide, only the presence of pyrochlore phase was observed independently of the annealing temperature. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: thin film; lead magnesium niobate; chemical method